Governance Mechanisms, Ownership Dynamics, and Capital Structure Determinants - Mochamad Rizky Pratama; Ratnawati, Kusuma (Jurnal Management Risiko dan Keuangan, 2025)
Purpose – This study aims to analyze the influence of corporate governance and ownership structure on the capital structure of infrastructure sector companies listed on the Indonesia Stock Exchange (IDX).     Design/methodology/approach – This quantitative study examines 21 infrastructure sector companies over a five-year period. Data were analyzed using SPSS version 29. Corporate governance is proxied by board size, the proportion of independent commissioners, and CEO duality, while ownership structure is represented by managerial ownership and ownership concentration.   Findings – The results show that board size and the proportion of independent commissioners have a significant positive effect on capital structure. CEO duality has a negative but insignificant effect. Managerial ownership has a significant negative effect on capital structure, whereas ownership concentration has a negative but insignificant effect.   Originality/value – This study contributes to the corporate finance and governance literature by demonstrating how corporate governance mechanisms and ownership structure influence capital structure decisions in Indonesia’s infrastructure sector, particularly in the context of post-pandemic financial challenges.